Impact of Rotational Speed and Oxygen Flow Rate on Homogeneity and Fluid Flow Patterns Using a CFD-Based Side Entry Mixer in the Aeration Process - Danawati Hari Prajitno; Ardista Izdhihar Kaloka; Hikmal Akbar H; Nuriya Shifa A; Vania Salma Fuadiyah; Happy Riezqya Dzunnurain (Institut Teknologi Sepuluh Nopember, 2026)
Mixing is an essential operation in many industrial processes to ensure uniform material distribution and enhance mass transfer. A side-entry mixer (SEM) is widely used in large storage tanks because it provides effective circulation with lower installation and maintenance costs than conventional top-entry mixers. This study investigated the effects of impeller rotational speed and oxygen flow rate on the homogeneity and flow patterns of a calcium carbonate (CaCO₃)–water suspension during the aeration process. Computational Fluid Dynamics (CFD) simulations using ANSYS and experimental visualization were employed to evaluate mixing performance. The operating conditions included impeller rotational speeds of 500, 600, 800, 1000, and 1200 rpm and oxygen flow rates of 5, 10, 15, 20, and 25 L/s. The results showed that increasing rotational speed and oxygen flow rate accelerated mixing and improved fluid homogeneity. The flow was dominated by axial and combined axial–radial patterns, promoting uniform circulation throughout the tank. Under the investigated conditions, the best mixing performance was achieved at 1200 rpm with oxygen flow rates of 20 and 25 L/s, reaching complete mixing within 40 s. Higher Reynolds and Sherwood numbers at these conditions also indicated enhanced turbulent mixing and mass transfer.